AGE-RELATED IMPAIRMENTS IN MEMORY AND IN CREB AND pCREB EXPRESSION IN HIPPOCAMPUS AND AMYGDALA FOLLOWING INHIBITORY AVOIDANCE TRAINING - Morris, Ken A. (2012)
This experiment examined whether age-related changes in CREB and pCREB contribute to the rapid forgetting seen in aged animals. Young (3-month-old) and aged (24-month-old) Fischer-344 rats received inhibitory avoidance training with a low (0.2 mA, 0.4 sec) or moderate (0.5 mA, 0.5 sec) footshock; memory was measured 7 days later. Other rats were euthanized 30 minutes after training, and CREB and pCREB expression levels were examined in the hippocampus, amygdala, and piriform cortex using immunohistochemistry. CREB levels decreased with age in the hippocampus and amygdala. After training with either shock level, young rats exhibited good memory and increases in pCREB levels in the hippocampus and amygdala. Aged rats exhibited good memory for the moderate but not the low shock but did not show increases in pCREB levels after either shock intensity. These results suggest that decreases in total CREB and in pCREB activation in the hippocampus and amygdala may contribute to rapid forgetting in aged rats. After moderate footshock, the stable memory in old rats together with absence of CREB activation suggests either that CREB was phosphorylated in a spatiotemporal pattern other than analyzed here or that the stronger training conditions engaged alternate mechanisms that promote long-lasting memory.